Development of an interactive tumor vascular suppression strategy to inhibit multidrug resistance and metastasis with pH/H2O2 responsive and oxygen-producing nanohybrids 1. Issue 31 (11th July 2019) - Du, Bin; Ding, Xiaoyu; Wang, Hui; Du, Qian; Xu, Tianguo; Huang, Jingshu; Zhou, Jie; Cheng, Genyang
Abstract : An ideal cancer therapeutic strategy should not only reverse multidrug resistance (MDR), but also prevent cancer metastasis. In this study, we address these cancer treatment challenges through an interactive vascular suppression strategy. Abstract : An ideal cancer therapeutic strategy should not only reverse multidrug resistance (MDR), but also prevent cancer metastasis. In this study, bovine serum albumin (BSA) was hybridized with Mn 2+ via biomineralization to develop a hybrid protein oxygen nanocarrier, which contained doxorubicin (DOX) and small interfering RNA (siRNA). The nanohybrid has the function of producing oxygen and chemotherapy synergistic gene therapy. FA–BSA–MnO2 /DOX/siRNA was favorable for increasing the sensitivity of MCF-7/ADR cells to DOX. Moreover, FA–BSA–MnO2 /DOX/siRNA NPs were also able to generate oxygen (O2 ) by reaction with endogenous hydrogen peroxide (H2 O2 ) in tumor, thereby down-regulating the expression of hypoxia inducible factor-1α (HIF-1α), and then the expression of the vascular endothelial growth factor (VEGF) was down-regulated. At the same time, siRNA can directly or indirectly suppress the expression of the VEGF and HIF-1α. Therefore, the combination of two pathways and the chemo-gene therapy strategy can interactively overcome tumor hypoxia-associated MDR and metastasis, which will enhance therapeutic efficacy in the future.